Zero waste engineering - Islam, Rafiqul, 1959- (Hoboken, N.J. : John Wiley & Sons ; Salem, Mass. : Scrivener Pub., 2012)
'The idea of'Zero-Waste Engineering' has been developing over years, in many areas of engineering, such as energy production (renewable energy), construction (green buildings), and many others. This book is a huge step in the continued march toward truly sustainable engineering practices. This book presents methods in various areas for sustainability purposes, such as new mathematical models, recyclable material selection, and renewable energy. Engineers and scientists of all industries will benefit from these principles of zero-waste engineering and how it applies to construction, energy production, and many other areas of engineering'--
'Explores new scientific principles on which sustainability and zero-waste engineering can be based Presents new models for energy efficiency, cooling processes, and natural chemical and material selection in industrial applications and business - Explains how'green buildings' and'green homes' can be efficiently built and operated with zero waste - Offers case histories and successful experiments in sustainability and zero-waste engineering'--
Includes bibliographical references and index.
Keywords: Waste minimization; TECHNOLOGY & ENGINEERING / Chemical & Biochemical